THE INFLUENCE OF THE TEACHER'S ROLE ON THE DISCIPLINE CHARACTER OF ALFA GENERATION CHILDREN AT GEDUNG REJO STATE PRIMARY SCHOOL - Najib, Khasbi Ainun; Nopitasari, Jihan; Mulyani, Putri (STIT Pringsewu, 2025)
This research aims to see the relationship between the role of teachers as mentors in cultivating the character of Generation Alpha children at Gedung Rejo State Elementary School, with the class teacher as the sample in this study. The alpha generation, which grew up in the digital era, faces various challenges in character formation, such as discipline, responsibility and empathy. This research uses a quantitative approach with interview and questionnaire methods to collect data from class V homeroom teachers at Gedung Rejo Elementary School. The data that has been collected is then tested by the researcher using the Correlation Test, in which case the researcher wants to see the relationship between the teacher's role as a student guide and the child's disciplinary character. In this research, the researcher obtained data from the homeroom teacher, the data was then processed and the researcher found a relationship between the role of the teacher and the child's disciplinary character, where the researcher found that the role of the teacher in guiding children to develop the disciplinary character of alpha generation children is very important for children growing up in this very sophisticated technological era. The results of this research show that the teacher's role as a character guide has a very significant influence on the development of children's character, especially on the discipline of alpha generation children.